2013
DOI: 10.1093/rpd/nct061
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial gamma radiation and its statistical relation with geological formation in the Mersing district, Johor, Malaysia

Abstract: An extensive survey was carried out for gamma dose rates (GDRs) in the Mersing district, Johor, Malaysia. The average value of GDR measured in the district was found to be 140 nGy h(-1), in the range of 40-355 nGy h(-1). The mean weighted dose rate to the population, annual effective dose equivalent, collective effective dose equivalent, lifetime cancer risk were 0.836 mSv y(-1), 0.171 mSv, 1.18 × 10(1) man Sv y(-1) and 6.98 × 10(-4) Sv y, respectively. An isodose map was produced for the district. One way ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Therefore, it is important to measure the dose rates at different geological areas (Martin & Harbinson, 1972). In the past years, several radiation surveys were carried out in many countries to measure outdoor terrestrial g radiation doses (Brígido, Caballero, Montalv an Estrada, Queipo García, S anchez, 1999;Gabdo, Ramli, Sanusi, Saleh, & Garba, 2014;Kapdan, Taskin, Kam, & Osmanlio glu, 2012;Morishima et al, 2000;Mustapha et al, 2013;Nizam, Ginnah, Rahman, Kamal, & Chowdhury, 2013;Otansev, Karahan, Kam, Barut, & Taskin, 2012;Pashazadeh, Aghajani, Nabipour, & Assadi, 2014;Saleh et al, 2013;Shahbazi-Gahrouei, 2003). Many rivers in India and other countries have been studied such as river Pannoiyar (Ramasamy, Suresh, Meenakshisundaram, & Gajendran, 2009), Palar (Ramasamy, Murugesan, & Mullainathan, 2006),Cauvery (Murugesan, Mullainathan, Ramasamy, & Meenakshisundaram, 2011;Ramasamy, Murugesan, & Mullainathan, 2004), Kali, Sharavathi, Netravathi (Narayana, Rajashekara, & Siddappa, 2007) and Godavari (Reddy, Reddy, Reddy, & Reddy, 2014) in India and Chao Phraya river in Thailand (Santawamaitre et al, 2011), Ribble Estuary in England (Punt, Tyler, Saleh, Bradley, & Copplestone, 2011) Ogun river in Nigeria (Jibiri & Okeyode, 2012) and river Pearl in China (Song, Chen, Tang, Zhang, & Xie, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to measure the dose rates at different geological areas (Martin & Harbinson, 1972). In the past years, several radiation surveys were carried out in many countries to measure outdoor terrestrial g radiation doses (Brígido, Caballero, Montalv an Estrada, Queipo García, S anchez, 1999;Gabdo, Ramli, Sanusi, Saleh, & Garba, 2014;Kapdan, Taskin, Kam, & Osmanlio glu, 2012;Morishima et al, 2000;Mustapha et al, 2013;Nizam, Ginnah, Rahman, Kamal, & Chowdhury, 2013;Otansev, Karahan, Kam, Barut, & Taskin, 2012;Pashazadeh, Aghajani, Nabipour, & Assadi, 2014;Saleh et al, 2013;Shahbazi-Gahrouei, 2003). Many rivers in India and other countries have been studied such as river Pannoiyar (Ramasamy, Suresh, Meenakshisundaram, & Gajendran, 2009), Palar (Ramasamy, Murugesan, & Mullainathan, 2006),Cauvery (Murugesan, Mullainathan, Ramasamy, & Meenakshisundaram, 2011;Ramasamy, Murugesan, & Mullainathan, 2004), Kali, Sharavathi, Netravathi (Narayana, Rajashekara, & Siddappa, 2007) and Godavari (Reddy, Reddy, Reddy, & Reddy, 2014) in India and Chao Phraya river in Thailand (Santawamaitre et al, 2011), Ribble Estuary in England (Punt, Tyler, Saleh, Bradley, & Copplestone, 2011) Ogun river in Nigeria (Jibiri & Okeyode, 2012) and river Pearl in China (Song, Chen, Tang, Zhang, & Xie, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This soil type is found in the Northern areas and smaller areas in the South and covered 1.2% of the Johor state (Saleh et al, 2013a). …”
Section: The Variations Between Gamma Dose Rates and Soil Typesmentioning
confidence: 88%
“…The readings were taken until they stabilised (Ramli, 1997;Saleh et al, 2013a). At least two measurements were taken around the measuring point using each of the two detectors.…”
Section: Measurements Of Gamma Radiation Dosementioning
confidence: 99%
“…It was found that the lithology of the sampling locations is of acid intrusive type. Soils formed from acid intrusives has higher radioactivity compared to other rock types [7,23,24]. Studies done in Pahang have shown that acid intrusives geology has high concentration of …”
Section: Determination Of Radiological Risks and External Hazard Indexmentioning
confidence: 99%